2000
DOI: 10.1006/viro.2000.0332
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus Infection of the Pancreas: Evaluation of Receptor Expression, Pathogenesis, and Immunopathology

Abstract: Coxsackievirus type B (CVB) infection of the pancreas induces a massive cellular infiltrate composed of natural killer cells, T cells, and macrophages and leads to the destruction of exocrine tissue. The physiological manifestations of pancreatic CVB infection are correlated with viral tropism; the virus infects acinar cells but spares the islets of Langerhans. Here we evaluate the mechanisms underlying pancreatic inflammation and destruction and identify the determinants of viral tropism. T-cell-mediated immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
101
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 49 publications
9
101
2
Order By: Relevance
“…Old mice infected with CVB3͞0 and adult and old mice infected with CVB3͞0 Old suffered significantly greater percent weight loss than adult mice infected with CVB3͞0 (P Ͻ 0.01) ( Table 2, which is published as supporting information on the PNAS web site). The weight loss observed in mice infected with CVB3͞0 Old was similar to weight loss observed by other investigators in mice after infection with CVB3 Nancy, a well characterized virulent CVB3 strain (34).…”
Section: Cvb3͞0 Old Infection Was Associated With Weight Loss High Vsupporting
confidence: 87%
See 2 more Smart Citations
“…Old mice infected with CVB3͞0 and adult and old mice infected with CVB3͞0 Old suffered significantly greater percent weight loss than adult mice infected with CVB3͞0 (P Ͻ 0.01) ( Table 2, which is published as supporting information on the PNAS web site). The weight loss observed in mice infected with CVB3͞0 Old was similar to weight loss observed by other investigators in mice after infection with CVB3 Nancy, a well characterized virulent CVB3 strain (34).…”
Section: Cvb3͞0 Old Infection Was Associated With Weight Loss High Vsupporting
confidence: 87%
“…Histological evaluation revealed that these foci were areas of fat necrosis and cellular infiltration. Previous investigators have reported that CVB3 can attack the adipose tissue in mice (34,40). Fat necrosis lesions were not observed as frequently in CVB3͞0-infected mice (0% adult, 29% old) as in CVB3͞0 Old -infected mice (29% adult, 71% old) throughout the perirenal, periadrenal, and gonadal adipose tissue.…”
Section: Cvb3͞0 Old Infection Was Associated With Weight Loss High Vmentioning
confidence: 71%
See 1 more Smart Citation
“…Collectively, these findings support the idea that enteroviruses have tropism to human islets and CAR production may be an important determinant of this tropism. It is also important to note that in the mouse, CAR production is completely the opposite to that seen here, being produced in exocrine pancreas but not in the islets [25]. This probably explains why enteroviruses preferentially infect exocrine pancreas in the mouse, but islets in humans.…”
Section: Discussionmentioning
confidence: 50%
“…CVBs also infect pancreatic acinar cells, often leading to pancreatic deficiency (4). Both mild and severe forms of acute pancreatitis are characterized by inflammation and edema of the exocrine pancreas, which constitutes ∼85% of the pancreas, and in the most severe form, tissue necrosis is also observed (5). A single attack of acute pancreatitis, which results in tissue damage and the loss of acinar cells, is normally followed by the recovery of the structure and function of the exocrine pancreas, suggesting that the pancreas has regenerative capacity after limited damage and tissue loss.…”
mentioning
confidence: 99%